1996
DOI: 10.1159/000267954
|View full text |Cite
|
Sign up to set email alerts
|

Measured Changes in Cataract over Six Months: Sensitivity of the NidekEAS-1000

Abstract: Lens opacities in 98 eyes from 63 consecutive outpatients with cataract were recorded by both retroillumination and Scheimpflug slit methods by one operator. This was repeated at 26 ± 1 weeks. Image analysis used the EAS-1000 software. Cortical and posterior subcapsular (PSC) cataracts were measured in retroillumination images as density more than 14 cct units below background density. Linear densitometry of white scattered light along the optical axis was measured for slit images by both peak density and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Foo and Maclean20 reported that the peak value and mean value of the lens density with Nidek EAS-1000 were able to present changes over a 6-month period in nuclear cataract but not in cortical or PSC cataract. Although the peak value of lens density was evaluated at one point of the entire lens nucleus, it may be considered as a representative index of the whole nucleus because, according to West and Taylor,21 NO is likely to be homogenous, and it is reasonable to suppose that visual impairment in nuclear cataract patients is most likely dependent on the opacity of the central nucleus rather than mean opacity.…”
Section: Discussionmentioning
confidence: 98%
“…Foo and Maclean20 reported that the peak value and mean value of the lens density with Nidek EAS-1000 were able to present changes over a 6-month period in nuclear cataract but not in cortical or PSC cataract. Although the peak value of lens density was evaluated at one point of the entire lens nucleus, it may be considered as a representative index of the whole nucleus because, according to West and Taylor,21 NO is likely to be homogenous, and it is reasonable to suppose that visual impairment in nuclear cataract patients is most likely dependent on the opacity of the central nucleus rather than mean opacity.…”
Section: Discussionmentioning
confidence: 98%
“…Although photographic image analysis densitometry, [14][15][16][17] or digital image analysis [18][19][20] as it becomes more widespread, might provide some more objective measures to enhance our preoperative assessment of cataracts and facilitate studies on progression of lens opacities, 21 the LOCSIII and other cataract grading systems have been shown to have high inter-observer and intra-observer repeatability 13,18,[22][23][24] and to demonstrate some consistency between different classifications. [24][25][26][27] New techniques such as photon spectroscopy for in vivo analysis of lenses remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing Scheimpflug and retroillumination digital photography with computerised analysis of lens opacities has allowed progression of cataract to be measured with great precision. [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] This method, cost effective for the large epidemiological studies, 89 is probably the best technique for recording cataract changes.…”
Section: Quantification Of Lens Opacity Measurements In Risk Factor Amentioning
confidence: 99%